2018
DOI: 10.1016/j.ekir.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation in Patients With Diabetic Nephropathy

Abstract: IntroductionComplement activation plays a role in various organs in patients with diabetes. However, in diabetic nephropathy (DN), the role of complement activation is poorly understood. We examined the prevalence and clinical significance of complement deposits in the renal tissue of cases with type 1 and type 2 diabetes with and without DN.MethodsWe measured the prevalence of glomerular C4d, C1q, mannose-binding lectin (MBL), and C5b-9 deposits in 101 autopsied diabetic cases with DN, 59 autopsied diabetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 43 publications
5
52
0
Order By: Relevance
“…27 In contrast, complement-mediated endothelial injury could also lead to podocyte injury. We previously reported that C4d is often present in the kidneys of patients with extensive endothelial injury, [28][29][30][31] and others have shown that complement activation is involved in endothelial injury in a variety of kidney diseases. [32][33][34][35] Experimental models have shown that podocyte damage can follow primary endothelial cell injury, 36 and subsequent podocyte depletion has been suggested as the final common pathway resulting in proteinuria and reduced estimated glomerular filtration rate.…”
Section: Time Course Of Glomerular C4d Deposition In Munich Wistar Frmentioning
confidence: 90%
“…27 In contrast, complement-mediated endothelial injury could also lead to podocyte injury. We previously reported that C4d is often present in the kidneys of patients with extensive endothelial injury, [28][29][30][31] and others have shown that complement activation is involved in endothelial injury in a variety of kidney diseases. [32][33][34][35] Experimental models have shown that podocyte damage can follow primary endothelial cell injury, 36 and subsequent podocyte depletion has been suggested as the final common pathway resulting in proteinuria and reduced estimated glomerular filtration rate.…”
Section: Time Course Of Glomerular C4d Deposition In Munich Wistar Frmentioning
confidence: 90%
“…DN has always been recognized as ESRD all over the world, which may be attributed to severe hyperglycemia [30]. Researches already evaluated the various treatments and therapeutic targets, which ameliorating renal fibrosis, including drugs, endocrine hormones, complement systems and miRNAs [8,[31][32][33]. However, these methods have different disadvantages, which hinder the efficacy of the clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients and animals with DKD exhibited kidney increase in C1q and C3 ( 28 , 29 ). Glomerular depositions of C1q, C4d, and C5b-9 in patients with DKD were more common than those without DKD, and glomerular depositions of C4d and C5b-9 were associated with the DKD severity ( 11 ). In our study, not only proteinuria but also the rate of DKD progression were significantly higher in biopsy-proven DKD patients with the glomerular immune complex of combined C4c with one or two of C3/C1q deposition than those with negative C4c deposits by the Kaplan-Meier survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported the association between complement component C4 and diabetes. Plasma C4 levels were associated with microvascular disease in diabetic patients ( 11 ). In addition, the serum C4 was significantly associated with the progression of Type 2 DKD ( 12 ).…”
Section: Introductionmentioning
confidence: 99%